Code Switching Found in “Maudy Ayunda Music” YouTube Channel - I G B Wahyu Nugraha Putra; Putu Devi Maharani; Sri Aryanti, Ni Kadek (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The use of two languages within a conversation has been known as code switching. This study analyzed the code switching phenomenon as found in Maudy Ayunda Music YouTube Channel. The goals are to analyze the types and functions of code switching. Poplack’s model (1980) is applied to identify the types of code switching; meanwhile, for the code switching function, it applied Appel & Muysken’s (1987) theory. The method of descriptive qualitative is used to identify the data. In collecting the data this study applied the observation method and note-taking techniques. Three chosen videos on Maudy Ayunda Music YouTube channel are used as the data source. Furthermore, the result of the study is presented in formal and informal method. All types of code switching were found; there were inter-sentential switching, tag switching and intra-sentential switching. And then, all functions of code switching also found; there were metalinguistic function, phatic function, directive function, poetic function, expressive function and referential function. Keywords: Code switching, YouTube, Maudy Ayunda